Investigating the effect of innovation capabilities on the relationship between international orientation and export performance - Hossein Norouzi; Mehdi Etemadi Far; Farzaneh Azmayesh Fard (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The purpose of this research is to achieve a better understanding of the development of organizational capabilities of knowledge-based companies and to improve their export performance. Also, this study aims to help the performance of these companies in international markets by measuring international orientation.Methodology: In order to achieve the stated goals, a questionnaire was distributed among 219 knowledge-based companies that had a history of exporting, of which the information of 205 questionnaires was used for analysis using structural equations and Smart PLS software.Findings: Based on the findings of this study, it can be seen that the three variables of international orientation, innovation capabilities and export performance have a positive and significant relationship with each other. It is also argued that the international orientation has an impact on six of the seven variable dimensions of innovation capabilities, and it does not have a significant relationship only with the dimension of research and development capacity. In addition, from these dimensions, only two dimensions of research and development capacity and marketing capacity have a significant relationship with export performance.Originality/Value: The results of this study confirm the findings of the previous literature, which acknowledged that there is a strong and positive relationship between the company's capabilities and their performance in international markets. This study provides insights into establishing international orientation as an important internal capability that can contribute to the superior export performance of these companies. The moderating effects are important because domestic drivers are found to influence the faster internationalization of new businesses.